Small Molecule RPI-194 Stabilizes Activated Troponin to Increase the Calcium Sensitivity of Striated Muscle Contraction - Mahmud, Zabed; Tikunova, Svetlana; Belevych, Natalya; Wagg, Cory S.; Zhabyeyev, Pavel; Liu, Philip B.; Rasicci, David V.; Yengo, Christopher M.; Oudit, Gavin Y.; Lopaschuk, Gary D.; Reiser, Peter J.; Davis, Jonathan P.; et al. (Frontiers in Physiology, 2022)
Small molecule cardiac troponin activators could potentially enhance cardiac muscle contraction in the treatment of systolic heart failure. We designed a small molecule, RPI-194, to bind cardiac/slow skeletal muscle troponin. (Cardiac muscle and slow skeletal muscle share a common isoform of the troponin C subunit.) Using solution NMR and stopped flow fluorescence spectroscopy, we demonstrate that RPI-194 binds to cardiac troponin with a dissociation constant KD of 6-24 uM, stabilizing the activated complex between troponin C and the switch region of troponin I. The interaction between RPI-194 and troponin C is weak (KD 311 uM) in the absence of the switch region. RPI-194 acts as a calcium sensitizer, shifting pCa50 from 6.28 to 6.99 in mouse slow skeletal muscle fibers and from 5.68 to 5.96 in skinned cardiac trabeculae at 100 uM concentration. There is also some cross-reactivity with fast skeletal muscle fibers (pCa50 increases from 6.27 to 6.52). In the slack test performed on the same skinned skeletal muscle fibers, RPI-194 slowed the velocity of unloaded shortening at saturating calcium concentrations, suggesting that it slows the rate of actin-myosin interactions. However, RPI-194 had no effect on the ATPase activity of purified actin-myosin. In isolated unloaded mouse cardiomyocytes, RPI-194 markedly decreased the velocity and amplitude of contractions. In contrast, cardiac function was preserved in mouse isolated perfused working hearts. In summary, the novel troponin activator RPI-194 acts as a calcium sensitizer in all striated muscle types. Surprisingly, it also slows the velocity of unloaded contraction, but the cause and significance of this is uncertain at this time. RPI-194 represents a new class of non-specific troponin activator that could potentially be used either to enhance cardiac muscle contractility in the setting of systolic heart failure or to enhance skeletal muscle contraction in neuromuscular disorders.